Antioxidant Capacities of Fractions of Bamboo Shaving Extract and Their Antioxidant Components - Gong, Jinyan (Molecules, 2016)
This research was conducted for evaluation of antioxidant activities of four fractions from bamboo shavings extract (BSE) and their antioxidant components. The antioxidant capacities of BSE and four fractions on ABTS, DPPH, FRAP and total antioxidant capacity assays exhibited the following descending order: DF > n-butanol fraction (BF) > BSE ≈ ethyl acetate fraction (AF) > water fraction (WF). Among the identified phenolic compounds, caffeic acid exhibited the highest antioxidant capacities on DPPH, FRAP and total antioxidant capacity assays. An extremely significant positive correlation between the antioxidant activities with the contents of total flavonoids, total phenolic acids, or total phenolics was observed in this study. The result indicated that the bamboo shaving extract and its solvent fractions could act as natural antioxidants in light of their potent antioxidant activities.